Python reinforcement learning projects : eight hands-on projects exploring reinforcement learning algorithms using TensorFlow /: eight hands-on projects exploring reinforcement learning algorithms using TensorFlow. (2018) - Saito, Sean; Yang, Wenzhuo; Shanmugamani, Rajalingappaa
No abstract available